Transplantation of Microglia in the Area of Spinal Cord Injury in an Acute Period Increases Tissue Sparing, but Not Functional Recovery - Akhmetzyanova, Elvira R.; Mukhamedshina, Yana O.; Zhuravleva, Margarita N.; Galieva, Luisa R.; Kostennikov, Alexander A.; Garanina, Ekaterina E.; Rizvanov, Albert A. (Frontiers in Cellular Neuroscience, 2018)
Microglial cells are known as important mediators of inflammation and immune response in the central nervous system (CNS). However, a neuroprotective role of these cells in post-traumatic processes should not be overlooked. Microglial cells are the first to respond to CNS injury and are further involved in all critical events of pathogenesis. When activated microglia clear the cellular debris and release anti- and proinflammatory cytokines and chemokines, nitric oxide, neurotrophins and antioxidants capable of producing both neurotoxic and neuroprotective effects. The aim of this study was to determine to what extent the phagocytic activity of microglia in an acute period of spinal cord injury (SCI) in rats can effect the post-traumatic processes. For this purpose we implanted genetically modified Ad5-EGFP or Ad5-GDNF microglial cells into the area of acute SCI. Our experiments demonstrate that the area of intact tissue was lower in the group transplanted with Ad5-GDNF-transduced microglial cells with reduced phagocytic activity than that in the group of animals transplanted with Ad5-EGFP-transduced microglia cells which did not affect the cell activity. At the same time, there was no significant difference in the functional recovery index between these groups. Thus, the increased number of microglia cells with good phagocytic activity in the area of acute SCI may contribute to the improved nervous tissue integrity without a significant effect on the functional recovery within 30 days after injury.